2019
DOI: 10.1111/jonm.12853
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership, job satisfaction and organizational commitment: The moderating effect of nurse tenure

Abstract: Aims To examine the associations between unit managers' authentic leadership with job satisfaction and organizational commitment and to investigate whether nurse tenure has a moderating effect on these associations. Background Authentic leaders create trusting relationships with their staff and help nurses become more satisfied with their jobs and committed to their organizations. Because nurses have different perceptions of their working environments based on their tenure, the effectiveness of managerial lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 51 publications
8
63
0
3
Order By: Relevance
“…This study involved a cross‐sectional secondary analysis. We used nurse survey data from the Shared Governance and Patient Activation Measure (SG‐PAM) study, which was conducted in Korea from April 2017 to March 2018 (Baek, Han, & Ryu, 2019). The SG‐PAM study originally aimed to examine the associations of nursing work‐related factors with nurses’ work outcomes and patient activation levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study involved a cross‐sectional secondary analysis. We used nurse survey data from the Shared Governance and Patient Activation Measure (SG‐PAM) study, which was conducted in Korea from April 2017 to March 2018 (Baek, Han, & Ryu, 2019). The SG‐PAM study originally aimed to examine the associations of nursing work‐related factors with nurses’ work outcomes and patient activation levels.…”
Section: Methodsmentioning
confidence: 99%
“…The SG‐PAM study originally aimed to examine the associations of nursing work‐related factors with nurses’ work outcomes and patient activation levels. Detailed information about the sampling techniques and data collection procedures for the SG‐PAM study is available elsewhere (Baek et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the transformational leadership style has been studied extensively: results showed its positive relationships with improved performance and reduced stress ( Dvir et al, 2002 ; Wang et al, 2011 ; Salem, 2015 ; Ng, 2017 ). Moreover, a growing body of evidence showed positive relationships between the authentic leadership style and several positive organizational outcomes, such as commitment, job satisfaction, creativity, innovativeness, and performance ( Khan, 2010 ; Azanza et al, 2013 ; Müceldili et al, 2013 ; Wong and Laschinger, 2013 ; Wang et al, 2014 ; Baek et al, 2019 ). An authentic leadership style is a positive approach to organizational leadership, characterized by self-awareness, relational transparency, authentic behaviors, and positive moral perspective ( Avolio and Gardner, 2005 ; Walumbwa et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation was found between the mean total score from the Ethical Leadership Scale and the work motivation of nurses in a study conducted byÖ zden et al (2017) [17]. Similarly, Baek et al (2019) reported a positive effect of leadership behavior and a positive perception of institutional climate on job satisfaction [18]. The basis of social learning theory is learning by observing others [19].…”
Section: Discussionmentioning
confidence: 93%